A curious occurrence of Hazenia broadyi spec. nova in Antarctica and the review of the genus Hazenia (Ulotrichales, Chlorophyceae) - Škaloud, P.; Nedbalová, L. (Linda); Elster, J. (Josef); Komárek, J. (Jiří) (Polar Biology, 2013)
Freshwater filamentous green algae with branched thalli are almost unknown from the Antarctic region. They have rarely been recorded from maritime Antarctica and from sub-Antarctic Islands with rich phanerogamic vegetation. In the genus Hazenia, only one unidentified species was reported from several subaerial sites on Signy Island in 1979. However, unique populations of this genus were recently found in the stony littoral zone of two stable shallow lakes in the northern deglaciated region of James Ross Island (NE Antarctic Peninsula). These populations have a specialized ecology; they participate in the microvegetation on the flattened surfaces of stones in the littoral zones of lakes. The dominant green filamentous and richly branched alga from these communities was transferred to monospecific culture and studied in detail. Based on distinct molecular, morphological, and ecological characters, this alga was described as a new species (Hazenia broadyi spec. nova).